MODUS VIVENDI: TRADITION IN TRANSITION, SHIFTING LANDSCAPE OF PESANTREN, AND RATIONALITY ON INDUSTRIALIZED COMMUNITIES - Mustofa, Imron; Hadi, Abd.; A’la, Bassam Abul (UIN Raden Mas Said Surakarta, 2024)
This study investigates substantial shifts in the rational paradigm and political identities in the Kaliwungu Industrial Area. Complexity, characterized by shifting values and emerging global identities, has co-opted the mode of existence of communities in sophisticated industrial countries. The dilemma between preserving local customs and the demands of globalization presents a distinct challenge. This study takes a qualitative approach, collecting data through approaches such as in-depth interviews, participatory observation, and critical analysis. Data sources are purposefully chosen from various strata of industrial society in order to acquire a comprehensive understanding. The investigation validates intriguing facts about Kaliwungu society. Based on the diffusion perspective, the result shows thatthere is a trend toward higher spiritual ideals in deciding societal positions, including political decisions. This plainly rules out the possibility of an exponential link between hedonism and industrialization. Furthermore, population movement from different origins to a given location is difficult, necessitating social harmonization and integration processes. Similarly, spiritual ideals, mental patterns, and social attitudes interact and change as a logical result of everyday exposure to modern values.